Bioethics and “Rightness” - Frank, Arthur W. (The Hastings Center report, 2017)
If bioethics seeks to affect what people do and don't do as they respond to the practical issues that confront them, then it is useful to take seriously people's sense of rightness. Rightness emerges from the fabric of a life—including the economy of its geography, the events of its times, its popular culture—to be what the sociologist Pierre Bourdieu calls a predisposition. It is the product of a way of life and presupposes continuing to live that way. Rightness is local and communal, holding in relationship those who share the same predisposing sense of how to experience. Rightness is an embodied way of evaluating what is known to matter and choosing among possible responses. Bioethics spends considerable time on what people should do and on the arguments that support recommended actions. It might spend more time on what shapes people's sense of the rightness of what they feel called to do.